Self-Fulfilling Debt Crises: A Quantitative Analysis - Bocola, Luigi; Dovis, Alessandro (American Economic Review, 2019)
This paper investigates the role of self-fulfilling expectations in sovereign bond markets. We consider a model of sovereign borrowing featuring endogenous debt maturity, risk-averse lenders, and self-fulfilling crises à la Cole and Kehoe (2000). In this environment, interest rate spreads are driven by both fundamental and nonfundamental risk. These two sources of risk have contrasting implications for the maturity structure of debt chosen by the government. Therefore, they can be indirectly inferred by tracking the evolution of debt maturity. We fit the model to Italian data and find that nonfundamental risk played a limited role during the 2008–2012 crisis. (JEL E43, E44, F34, G01, G15, H63)